Perioperative outcomes and risk assessment in dialysis patients: current knowledge and future directions. Issue 6 (11th June 2019) - Palamuthusingam, Dharmenaan; Johnson, David W.; Hawley, Carmel M.; Pascoe, Elaine; Sivalingam, Pal; Fahim, Magid
Abstract: Perioperative medicine is rapidly emerging as a key discipline to address the specific needs of high‐risk surgical groups, such as those on chronic dialysis. Crude hospital separation rates for chronic dialysis patients are considerably higher than patients with normal renal function, with up to 15% of admission being related to surgical intervention. Dialysis dependency carries substantial mortality and morbidity risk compared to patients with normal renal function. This group of patients has a high comorbid burden and complex medical need, making accurate perioperative planning essential. Existing perioperative risk assessment tools are unvalidated in chronic dialysis patients. Furthermore, they fail to incorporate important dialysis treatment‐related characteristics that could potentially influence perioperative outcomes. There is a dearth of information on perioperative outcomes of Australasian dialysis patients. Current perioperative outcome estimates stem predominantly from North American literature; however, the generalisability of these findings is limited, as the survival of North American dialysis patients is significantly inferior to their Australasian counterparts and potentially confounds reported perioperative outcomes; let alone regional variation in surgical indication and technique. We propose that data linkage between high‐quality national registries will provide more complete data with more detailed patient and procedural information to allow for more informative analyses to develop and validate dialysis‐specific risk assessment tools.